The Classroom teacher's guide to instructional and curricular modifications [videorecording].1, modifications 101 making the curriculum accessible to all students. - Dover, Wendy Fetner; Master Teacher (Manhattan, Kan. Master Teacher, 2006)
Provides a framework for teachers to work through the barrier issues of modification, suggests ways to share information while respecting confidentiality, and gives ways to approach assessment accommodations and modifications.
"Featuring Wendy Fetner Dover."--Container cover.
Keywords: Chilren with disabilities -- Education -- United States; Mainstreaming in education -- United States; Classroom management -- United States; Curriculum planning -- United States